(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The object of this work is to analyse the new crimes against traffic safety contained in the Law of Modification of the Spanish Penal Code 1995, as for road safety. First, the work tackles the interpretative difficulties that arise from the new regulation contained in article 379, which establishes a fixed level of alcohol in the bloodin order to determine the typical relevance of the behaviour in the crime of drivingunder the influence of alcohol and other substances. Then, the work analyses the problems that this figure, as well as the new dispositions relative to driving at high speed and the driving without a driver’s license, raise in relation to the demands ofthe principles of harm, proportionality and minimal intervention.